HALOGEN ELEMENTS AND THEIR IMPORTANCE IN LIVING ORGANISMS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
A wider study of the importance of each element in living organisms. Wider application of the biological significance of the functioning of halogens. Production of a database for students. Processing and discussion of the information we know and do not know. Deeper study of the importance of macro and microelements in the body